Pengaruh Pemberian Kompos Kulit Kopi Dan Pupuk NPK Terhadap Pertumbuhan Dan Produksi Tanaman Kedelai (Glycine max L. Merril) (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to determine the growth and production of soybean plants by composting coffee rind and NPK as well as getting the best dose. This research has been conducted at the Faculty of Agriculture Experimental Station Riau University Campus Bina Widya km 12.5 Simpang Baru Kecamatan Tampan Kotamadya Pekanbaru, for three months, from April to July 2017. This study used a factorial randomized block design (RBD). The first factor was coffee rind compost consisting of 3 levels, K0= 0 ton/ha, K1= 10 ton/ha, K2= 20 ton/ha and the second factor, namely NPK consists of 4 levels, P1= 62,5 kg/ha, P2= 125 kg/ha, P3= 187,5 kg/ha, P4= 250 kg/ha. The parameters observed consisting of plant height, number of productive branches, days to flowering, number of flowers, harvesting age, the percentage of pithy pods, number of seeds per plant, crop seed weight, yield per m2 and weight of 100 seeds. Results of analysis of variance followed by DNMRT  5%. Coffee rind compost 10 ton/ha and 125 kg NPK/ha increased plant height, number of seeds per plant, seed weight per plant and yield per m2.Keywords: Soybean, coffee rind compost, NPK.